Superficial migratory thrombophlebitis in a 10-year-old girl. - Bonifazi, E.; Milano A. Garofalo, L. (European Journal of Pediatric Dermatology, 2011)
Migratory thrombophlebitis (MT) is a recurrent episodic segmental thrombosis of the superficial veins of the limbs and trunk. Rare in the child, in which may be related to trauma or infections, MT is more frequent in the adult, in which it may be associated with pathological conditions of various types including neoplasms. This association is also called Trousseau’s syndrome, named after the doctor who first diagnosed MT on himself, linking it with an adenocarcinoma of the pancreas who later brought him to death.